Broad-spectrum antifungal activity of C12/C14 alkyl triphenylphosphonium salts (TPP-C12 and TPP-C14) against clinically relevant pathogens - Geng, Yuanyuan; Wang, Xiaohui; Zhang, Shu; Liu, Xuelian; Liu, Huihui; Guo, Xiaonan; Lu, Yangzhen; Gong, Jie; Qin, Zhaohai (Frontiers in Microbiology, 2026)
IntroductionHuman fungal infections affect billions of people and result in more than 2 million deaths every year, however, they have historically been neglected as a cause of infectious disease-related deaths worldwide. Fungal drug resistance has become an increasingly serious problem with the wide use of antifungal drugs and the adaptive evolution of fungi. Resistance to all commonly used antifungal drugs has been reported, and the development of non-traditional antifungal drugs is urgently needed.MethodsMinimal inhibitory concentrations (MICs) of clinical pathogenic fungi were assessed by broth dilution antifungal susceptibility testing. One hundred and twenty eight yeast strains and 66 filamentous strains were used, including C. albicans resistant and susceptible to azoles, C. tropicalis, C. auris, C. krusei, the C. glabrata complex, the C. haemulonii complex, the C. parapsilosis complex, Cryptococcus neoformans, Aspergillum, Trichophyton, and dimorphic Sporothrix globosa. Further RNAseq was performed to explore the antifungal mechanism of two derivatives.ResultsTwo derivatives of the mitochondrion-targeted compound triphenylphosphonium (TPP), TPP-C12 and TPP-C14, showed broad-spectrum antifungal activity. The MIC against yeast strains was 1.5173 and 1.0109 mg/L, respectively. For filamentous strains, the MIC ranges were 2–8 mg/L for both compounds. For the dimorphic Sporothrix globosa, the GM values were 1.0134 and 1.0816 mg/L, respectively. RNAseq revealed that the derivatives interfered with mainly mitochondrial and ribosomal functions. Through coregulation of mitochondrial and nuclear genes, the derivatives cause mitochondrial dysfunction and ultimately cell death.DiscussionTaken together, the findings show that TPP-C12 and TPP-C14 are stable, effective, and broad-spectrum antifungal agents with no species or strain specificity.